2014
DOI: 10.1021/je500349v
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability Boundaries and Structures of Methane + Monohalogenated Cyclopentane Mixed Hydrates

Abstract: Thermodynamic stability boundaries of the mixed hydrate composed of methane and fluorocyclopentane, chlorocyclopentane, or bromocyclopentane were investigated in a temperature range of (274.17 to 306.19) K and pressures up to 9.93 MPa under the four-phase (hydrate, aqueous, monohalogenated cyclopentane-rich liquid, and gas phases) equilibrium conditions. Also, the crystal structure of the methane + chlorocyclopentane hydrate was determined by means of powder X-ray diffractometry. The each boundary is laid at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…At low pressures and low temperatures, the equilibrium data of the CH 4 +c-C 5 H 9 Br mixed hydrate system have been reported. 6,8 The equilibrium data plotted by solid keys below 80 MPa would be smoothly connected to the reported data 6,8 in the low-pressure region. Raman spectra derived from the CH 4 and c-C 5 H 9 Br molecules in the hydrate phase are shown in Figure 2, which is accompanied by the Raman spectra corresponding to the intermolecular vibration between water molecules (lattice mode).…”
Section: ■ Results and Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…At low pressures and low temperatures, the equilibrium data of the CH 4 +c-C 5 H 9 Br mixed hydrate system have been reported. 6,8 The equilibrium data plotted by solid keys below 80 MPa would be smoothly connected to the reported data 6,8 in the low-pressure region. Raman spectra derived from the CH 4 and c-C 5 H 9 Br molecules in the hydrate phase are shown in Figure 2, which is accompanied by the Raman spectra corresponding to the intermolecular vibration between water molecules (lattice mode).…”
Section: ■ Results and Discussionsupporting
confidence: 69%
“…The reaction products (c-C 5 H 8 and c-C 5 H 9 OH) are also enclathrated because it is reported that the c-C 5 H 8 molecule is enclathrated in the 5 12 6 4 -cage of s-II hydrate. 17,18 Moreover, the four-phase equilibrium curves in the CH 4 +c-C 5 H 8 and CH 4 +c-C 5 H 9 OH mixed hydrate systems are laid at a pressure lower (a temperature higher) than that in the CH 4 +c-C 5 H 9 Br system, 6,8 as shown in Figure 5 (Supporting Information, Table S1). The drastic change of the Raman spectrum in Figure 2a indicates that c-C 5 H 8 and c-C 5 H 9 OH as well as a quite small amount of c-C 5 H 9 Br competitively occupy the 5 12 6 4 -cages of the s-II hydrate in this system.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The pattern clearly indicates that the Xe+C 6 H 6 mixed hydrate is the sII (cubic, Fd 3 m ). The obtained lattice parameter recorded at 153 K and 0.1 MPa is a = (1.732 ± 0.001) nm, which falls into the category of sII hydrates having slightly larger lattice constant, even in view of their thermal expansivities. …”
Section: Resultsmentioning
confidence: 89%